The Pivotal Role of DNA Repair in Infection Mediated-Inflammation and Cancer - Sahan, Ayse Z.; Hazra, Tapas K.; Das, Soumita (Frontiers in Microbiology, 2018)
Pathogenic and commensal microbes induce various levels of inflammation and metabolic disease in the host. Inflammation caused by infection leads to increased production of reactive oxygen species (ROS) and subsequent oxidative DNA damage. These in turn cause further inflammation and exacerbation of DNA damage, and pose a risk for cancer development. H. pylori-mediated inflammation has been implicated in gastric cancer in many previously established studies, and F. nucleatum presence has been observed with greater intensity in colorectal cancer patients. Despite ambiguity in the exact mechanism, infection-mediated inflammation may have a link to cancer development through an accumulation of potentially mutagenic DNA damage in surrounding cells. The multiple DNA repair pathways such as base excision, nucleotide excision, and mismatch repair that are employed by cells are vital in the abatement of accumulated mutations that can lead to carcinogenesis. For this reason, understanding the role of DNA repair as an important cellular mechanism in combatting the development of cancer will be essential to characterizing the effect of infection on DNA repair proteins and to identifying early cancer biomarkers that may be targeted for cancer therapies and treatments.